Climate Change, Soil Salinity, and the Economics of High-Yield Rice Production in Coastal Bangladesh - Dasgupta, Susmita; Hossain, Md. Moqbul; Huq, Mainul; Wheeler, David (World Bank Group, Washington, DC, 2015)
It is a virtual certainty that sea-level rise will continue throughout the century and beyond 2100 even if greenhouse gas emissions are stabilized in the near future. Understanding the economic impacts of salinity intrusion thus is essential for planning adaptation in low-lying coastal areas around the world. This paper presents a case study in Bangladesh on how climate change leads to the spread of soil salinity and the impact on agricultural production in the coastal region. The analysis is conducted in two stages. The first stage predicts future soil salinity for 69 subdistricts, taking into account climate-induced changes in river salinity, temperature, and rainfall by 2050. The second stage uses econometric analysis to predict the impact of climate-induced increases in soil salinity on the output and price of high-yielding-variety rice. The findings indicate output declines of 15.6 percent in nine subdistricts where soil salinity will exceed 4 deciSiemens per meter before 2050. Without newly developed coping strategies, the predicted changes will produce significant income declines from high-yielding-variety rice production in many areas, including a 10.5 percent loss in Barisal region and a 7.5 percent loss in Chittagong region.